2017
DOI: 10.1371/journal.pone.0173979
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Bifidobacterium bifidum G9-1 alleviates rotavirus gastroenteritis through regulation of intestinal homeostasis by inducing mucosal protective factors

Abstract: Human rotavirus (RV) infection is a leading cause of dehydrating diarrhea in infants and young children worldwide. Since therapeutic approaches to RV gastroenteritis are limited to alleviation of dehydration with oral rehydration solutions, more direct approaches to palliate symptoms of RV gastroenteritis are required. Treatments with probiotics have been increasingly recognized as alternative safe and low cost treatments for moderate infectious diarrhea. In this study, Bifidobacterium bifidum G9-1 (BBG9-1), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…BBG9-1 ( Bifidobacterium bifidum G9-1; Biofermin R&D Center, Kobe, Japan) 11 was obtained from the Culture Collection of Biofermin Pharmaceutical Co., Ltd. and cultured at 37 °C for 18 h in GAM Broth (Nissui Pharmaceutical. Co., Ltd., Tokyo, Japan) supplemented with 0.7% glucose and 0.1% Tween 80.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BBG9-1 ( Bifidobacterium bifidum G9-1; Biofermin R&D Center, Kobe, Japan) 11 was obtained from the Culture Collection of Biofermin Pharmaceutical Co., Ltd. and cultured at 37 °C for 18 h in GAM Broth (Nissui Pharmaceutical. Co., Ltd., Tokyo, Japan) supplemented with 0.7% glucose and 0.1% Tween 80.…”
Section: Methodsmentioning
confidence: 99%
“…BBG9-1 isolated from a healthy individual has been used as an intestinal medicine for several decades. Furthermore, we have recently reported that BBG9-1 has a mucosal protective effect against virus-induced enteritis 11 and can attenuates anti-cancer drug-induced inflammation by helping to ameliorate dysbiosis 12 . Accordingly, we were motivated to examine the effect of BBG9-1 in an animal model of IBS.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the 16S rDNA of the fecal microbiome was performed according to a method described previously [ 28 ] with minor modifications. Briefly, the V3-V4 region of 16S rDNA was amplified using the primers, as reported previously [ 28 ], and then ligated with overhang Illumina adapter consensus sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the 16S rDNA of the fecal microbiome was performed according to a method described previously [ 28 ] with minor modifications. Briefly, the V3-V4 region of 16S rDNA was amplified using the primers, as reported previously [ 28 ], and then ligated with overhang Illumina adapter consensus sequences. The PCR was performed once at 95 °C for 3 min and then for 25 cycles at 95 °C for 30 s, 55 °C for 30 s, and 72 °C for 30 s, and finally at 72 °C for 5 min on a Veriti thermal cycler (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…2,3 In underdeveloped countries, enteric bacteria such as Escherichia coli, Campylobacter, Shigella, Vibrio cholerae, Salmonella, viruses such as Rotavirus, Human caliciviruses, and parasites like Cryptosporidium parvum, Giardia intestinalis, Entamoeba histolytica, Cyclosporacayetanensis are major pathogens to cause diarrhea. [4][5][6] Diarrhea results in higher amount of water losses that may lead to death, if left untreated. 1 Oral rehydration solutions (ORS) have been found to decrease the incidence of mortality and morbidity caused by diarrhea; but ORS did not have any effect on the duration of the disease, consistency of the stools, and gastrointestinal flora.…”
Section: Introductionmentioning
confidence: 99%